Bakti Sosial Penanaman 700 Bibit Pohon Buah Pada Desa Lumban Bul-Bul Kecamatan Balige Kabupaten Toba - Damanik, Evo Marisi Tumpal; Simarmata, Bangettua; Sitanggang, Mery Suliyanti H.; Girsang, Tonggo Sangap Timbul (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Balige District is one of the hometowns of one of the students of the Bina Prestasi Independent Polytechnic. The selection of this location was agreed to be the place for Community Service because it is to realize the